IDENTIFIKASI MISKONSEPSI MAHASISWA PGMI PADA KONSEP HUKUM NEWTON MENGGUNAKAN CERTAINTY OF RESPONSE INDEX (CRI) - Muna, Izza Auliyatul (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: The extent to whichstudent difficulties in understanding the basic concepts of physics has been a majorissue for teachers and practitioners in the field of physics teaching. The symptom of misconceptionoften interferes with the learning process, especially for students when they are required to accommodatethe knowledge. The way how to identify the occurrence of misconception among students as well as to distinguish it with having no idea ofÂ Â  the concept is by occupying the method of Certainty of Response Index (CRI). It is widely asserted that misconception may become the scourge in the teaching of physics and other sciences, because its existence is believed to inhibit the process of assimilation of new knowledge among students. Misconceptionis supposed to be formed in childhood brain in interaction with the surrounding nature. The problem thatmight arise when thetreatment made is thatit is difficult to distinguish whether the students are experiencing misconceptions or just having absent concept. This is because the way to treat students who have misconception will be very different from that of treating students who do not know the concept. Hence, CRI is developed to identify the occurrence of misconception as well as to distinguish it from having absent concept. Generally, CRI can be interpreted as a measure of the level of respondentsâ confidence/ assurance in answering the questions provided.